Adenoviral TMBIM6 vector attenuates ER-stress-induced apoptosis in a neonatal hypoxic-ischemic rat model - Desislava Doycheva; Ningbo Xu; Harpreet Kaur; Jay Malaguit; Devin William McBride; Jiping Tang; John H. Zhang (The Company of Biologists, 2019)
Endoplasmic reticulum (ER) stress is a major pathology encountered after hypoxic-ischemic (HI) injury. Accumulation of unfolded proteins triggers the unfolded protein response (UPR), resulting in the activation of pro-apoptotic cascades that lead to cell death. Here, we identified Bax inhibitor 1 (BI-1), an evolutionarily conserved protein encoded by the transmembrane BAX inhibitor motif-containing 6 (TMBIM6) gene, as a novel modulator of ER-stress-induced apoptosis after HI brain injury in a neonatal rat pup. The main objective of our study was to overexpress BI-1, via viral-mediated gene delivery of human adenoviral-TMBIM6 (Ad-TMBIM6) vector, to investigate its anti-apoptotic effects as well as to elucidate its signaling pathways in an in vivo neonatal HI rat model and in vitro oxygen-glucose deprivation (OGD) model. Ten-day-old unsexed Sprague Dawley rat pups underwent right common carotid artery ligation followed by 1.5 h of hypoxia. Rat pups injected with Ad-TMBIM6 vector, 48 h pre-HI, showed a reduction in relative infarcted area size, attenuated neuronal degeneration and improved long-term neurological outcomes. Furthermore, silencing of BI-1 or further activating the IRE1α branch of the UPR, using a CRISPR activation plasmid, was shown to reverse the protective effects of BI-1. Based on our in vivo and in vitro data, the protective effects of BI-1 are mediated via inhibition of IRE1α signaling and in part via inhibition of the second stress sensor receptor, PERK. Overall, this study showed a novel role for BI-1 and ER stress in the pathophysiology of HI and could provide a basis for BI-1 as a potential therapeutic target.